Haptic Manipulation of Deformable Objects in Hybrid Bilateral Teleoperation System - Juan Manuel Ibarra-Zannatha; Claudia Marmolejo-Rivas; Manuel Ferre-Pérez; Rafael Aracil-Santonja; Salvador Cobos-Guzmán (Applied Bionics and Biomechanics)
The aim of this work is the integration of a virtual environment containing a deformable object, manipulated by an open kinematical chain virtual slave robot, to a bilateral teleoperation scheme based on a real haptic device. The virtual environment of this hybrid bilateral teleoperation system combines collision detection algorithms, dynamical, kinematical and geometrical models with a position–position and/or force–position bilateral control algorithm, to produce on the operator side the reflected forces corresponding to the virtual mechanical interactions, through a haptic device. Contact teleoperation task over the virtual environment with a flexible object is implemented and analysed.